CHARACTERISTICS OF DAILY WATER TEMPERATURE FLUCTUATIONS IN LAKE KIERSKIE (WEST POLAND) - Ptak, Mariusz; Sojka, Mariusz; Nowak, Bogumił (Quaestiones Geographicae, 2019)
The paper presents the dynamics of daily water temperature fluctuations in Lake Kierskie (West Poland) and determines the effect of air temperatures and wind speed on the variability of the parameter (water temperature). The analysis was based on hourly water temperature values from the period from May 2012 to January 2018. The data analysis permitted the description of the thermal regime of waters in the lake in the hourly cycle in reference to each month, and designation of months characterised by the highest and lowest stability of water temperatures. More than half of the analysed days was characterised by a change in water temperature not exceeding 1°C. The course of water temperature showed strongly positive correlations with air temperature, and weak correlations with wind speed. Water temperatures in the lake were correlated the strongest with air temperatures with a 24 h time step.